Synergistic Immuno Photothermal Nanotherapy (SYMPHONY) for the Treatment of Unresectable and Metastatic Cancers - Yang Liu (Nature Portfolio, 2017)
Abstract Metastatic spread is the mechanism in more than 90 percent of cancer deaths and current therapeutic options, such as systemic chemotherapy, are often ineffective. Here we provide a proof of principle for a novel two-pronged modality referred to as Synergistic Immuno Photothermal Nanotherapy (SYMPHONY) having the potential to safely eradicate both primary tumors and distant metastatic foci. Using a combination of immune-checkpoint inhibition and plasmonic gold nanostar (GNS)–mediated photothermal therapy, we were able to achieve complete eradication of primary treated tumors and distant untreated tumors in some mice implanted with the MB49 bladder cancer cells. Delayed rechallenge with MB49 cancer cells injection in mice that appeared cured by SYMPHONY did not lead to new tumor formation after 60 days observation, indicating that SYMPHONY treatment induced effective long-lasting immunity against MB49 cancer cells.